Longer Life and Healthy Aging - Zeng, Yi; Crimmins, Eileen M.; Carrière, Yves; Robine, Jean-Marie (International Studies in Population, 2006)
A fundamental issue facing the global community is meeting the challenges of population aging and achieving healthy aging to maintain an active older population and reduce the number of disabled people. The focus of this book is on theoretical issues and empirical findings related to trends and determinants of healthy aging, including factors related to "healthy longevity" of the oldest-old, aged 80 and over. The group is the most rapidly increasing elderly sub-population and is most likely to need assistance in daily living in all countries. Chapters include both longitudinal and cross-sectional data from North America, Europe, and Asia in country-specific studies and cross-national comparisons. Part I focuses on the definition, components, concepts, measurements, and determinants of healthy aging, and discusses the trends and patterns of disability and healthy life expectancy at the macro level. Part II addresses individual healthy aging, including its biological and socio-demographic aspects. Part III focuses on issues concerning the family and healthy aging, and Part IV explores formal and informal care for healthy aging through governmental policy interventions and community service programs.